Tuberous sclerosis. Case presentation. - Graciela Caridad Cabrera Acea; Ana Dolores López Marquet (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
A mixed race female, 34 years of age was attended due to papule lesions in the facial area between one and ten mm of diameter. These lesions were flat, with skin colour, symmetrically distributed in the central part of the face (cheeks, chin and nose), of soft texture with telangiectasia. She referred to present these lesions since she was seven years of age, and three months before attending to consultation she noticed an increase in the number and size of these lesions. The patient has a normal intelligence coefficient and declared family history of these lesions. The diagnosis was sebaceous adenoma. Since this is not a frequent disease and due to the patient's age we decided to publish this case.